Professional Ruby on Rails - Rappin, Noel
Nothing less than a revolution in the way web applications are constructed,Ruby on Rails (RoR) boasts a straightforward and intuitive nature that avoids programming repetition and makes it infinitely easier to build for the web. This book captures the current best practices to show you the most efficient way to build a spectacular web application with RoR. You?ll learn everything you need to know in order to extend Rails so that you can take advantage of the many exciting and wonderful things that are being done by the diligent RoR programming community